Length – Weight Relationship Analysis and Condition Factor Blood Clams (Anadara granosa) In Panipahan, Rokan Hilir Regency, Riau Province - Asmita, Manja; Machrizal, Rusdi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
This research was conducted in the Rokan Hilir district with the aim of analyzing the length-weight relationship and condition factors of blood clams (Anadara granosa). The benefit of this research is to provide information about the length of weight and condition factors of A. granosa which can be used as a reference in cultivation and further research. This research was carried out for 90 days from October to December 2021, in the waters of Panipahan, Rokan Hilir Regency. This length-weight relationship was calculated using a linear allometric model (LAM), while the condition factor was calculated using the Fulton formula (K) and relative weight (Wr). The results of the analysis of the length-weight relationship of blood clams get a value of b <3 = 0.894, which is a negative allometric where the increase in length is faster than the growth in weight. With the value of relative weight (Wr) 71,325-149,883 and Fulton’s condition factor (K) 75,372-387,106. This is caused by environmental conditions that are quite good in supporting blood clams (A. granosa) . in the waters of Panipahan Kab. Rokan Hilir